Comparison of treatment outcomes in lumbar disc herniation patients treated with epidural steroid injections: interlaminar versus transforaminal approach. (March 2020) - Bensler, Susanne; Walde, Melissa; Fischer, Michael A; Pfirrmann, Christian WA; Peterson, Cynthia K; Sutter, Reto
Background: The study describes the difference of pain reduction in interlaminar and transforaminal injections. Purpose: To compare treatment outcomes after interlaminar versus transforaminal epidural steroid injections in patients with disc herniations at the level L3/4–L5/S1 and analyze associated magnetic resonance imaging (MRI) findings. Material and Methods: This retrospective comparative effectiveness outcome study included 198 patients with computed tomography (CT)-guided interlaminar (n = 99) or transforaminal (n = 99) epidural injections with particulate steroids. Pain levels at baseline and one day, one week, and one month after injection were assessed using the 11-point Numerical Rating Scale for Pain. Overall improvement was assessed after one day, one week, and one month using the Patients Global Impression of Change. MRI analysis was performed by two radiologists. Student's t-test, Chi-square test, and Fisher's exact test were calculated. Results: Baseline pain scores were equal for interlaminar and transforaminal injections (6.23, SD = 2.10 vs. 5.84, SD = 2.02; P  = 0.18). There were no significant differences in improvement between the interlaminar and transforaminal approach of epidural steroid injections after one day (30.5% vs. 21.2%, P  = 0.432), one week (41.7% vs. 40.8%, P  = 1.000), and one month (53.3% vs. 43.9%, P  = 0.322), but there was a trend towards better effect of interlaminar injections at one day and one month. The change in Numerical Rating Scale for Pain scores showed no significant differences between the two cohorts after one day, one week, and one month ( P  ≥ 0.115). None of the MR findings predicted a better or worse outcome ( P  ≥ 0.171). Conclusion: Interlaminar and transforaminal injections with particulate corticosteroids were equally effective, with a non-significant advantage of interlaminar injections at one day and one month. None of the MR findings were associated with treatment outcomes.